2019
DOI: 10.1111/imj.14256
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes in physician practice: a complex debate

Abstract: E‐cigarettes, or electronic nicotine delivery systems (ENDS), have been suggested as a potential aid for smoking cessation, but many questions about their efficacy and safety remain unanswered. Until very recently, the evidence for ENDS in smoking cessation was largely based on observational studies or randomised controlled trials with methodological flaws and did not provide adequate evidence to support strongly ENDS for smoking cessation. Concerns about the uptake of ENDS by nonsmoking populations (such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…NRT bought over‐the‐counter) [ 14 ]. However, whether health professionals should be recommending e‐cigarettes to smokers remains an issue of some debate in the medical community [ 17 , 18 ], with clinicians unaware or unconvinced by the evidence on efficacy and concerned by possible long‐term health effects [ 19 , 20 ]. Several organizations in the United Kingdom, including Public Health England, the Royal College of Physicians and the Royal College of General Practitioners, now recommend that clinicians give advice on e‐cigarettes as one option to help their patients quit smoking [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…NRT bought over‐the‐counter) [ 14 ]. However, whether health professionals should be recommending e‐cigarettes to smokers remains an issue of some debate in the medical community [ 17 , 18 ], with clinicians unaware or unconvinced by the evidence on efficacy and concerned by possible long‐term health effects [ 19 , 20 ]. Several organizations in the United Kingdom, including Public Health England, the Royal College of Physicians and the Royal College of General Practitioners, now recommend that clinicians give advice on e‐cigarettes as one option to help their patients quit smoking [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important point as e-cigarettes have bypassed the usual manner of phased trials to licensing and as such there is ongoing work to try and understand the place that they may have within public health. 19…”
Section: Resultsmentioning
confidence: 99%
“…Overall, this result seems to offer some basis for e-cigarette use possibly in the context of tailored support in reducing tobacco consumption. 19 In the Efficiency and Safety of an ECLAT trial that involved 300 current smokers with no intention to quit, participants were randomised between 7.2 mg/5.4 mg e-cigarettes and non-nicotine cigarettes; the results showed decreased cigarette consumption (confirmed by self-assessment and eCO measurement) and sustained abstinence but was once again limited by its small study size and not significant size effect. 12 Furthermore, a Cochrane systematic review suggested that the small number of RCTs and wide confidence intervals meant that no definitive conclusion could be made but did show that patients would likely reduce consumption when using e-cigarettes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations